Instruments and Data Logger for Measuring Electrical Parameters: Indonesian Market Review and Research Direction - Wibawa, Agus Satrya; Kumara, I Nyoman Satya; Sukerayasa, I Wayan (Journal of Electrical, Electronics and Informatics, 2020)
Electrical parameters such as voltage, current, power, energy, frequency, and power factor are parameters needed in the operation of an electrical system and machinery. The measurement results provide an overview of the system performance and indicator of abnormal or faulty operations. Nowadays, the electrical parameter instruments grow rapidly with a wide range of features and capability, started from analog instruments to digital measurement with data logging features. This paper reviews the availability of electrical parameter instruments and data logger systems in Indonesia. The review includes technical specifications of instruments, manufacturers, vendors, and data logging features. The data were obtained from vendor publications, manufacturers, scientific publications, and e-commerce websites in Indonesia. The information regarding the availability of the instruments and data logger systems will provide a quick reference in choosing instruments for a certain application to suit the purpose of the measurement and also the cost of the device. Moreover, the information also can provide benchmarks for research and development of low-cost multichannel data logging systems with additional features such as remotely accessible through the implementation of the internet of things .